System- and fish-size-specific reference intervals for plasma analytes in Atlantic salmon (Salmo salar L.) reared in commercial fresh- and saltwater recirculating aquaculture systems: a descriptive study - Thomas Amlie; David Persson; Simen Foyn Nørstebø; Asgeir Østvik; Marit Stormoen; Øystein Evensen (Frontiers in Aquaculture)
IntroductionIn aquaculture, clinical chemistry can be used pre-emptively to manage fish health and for early disease intervention. While less established in farmed fish compared to farmed terrestrial animals, it has been used for salmonid cage farming but is almost non-existent in recirculation aquaculture systems (RAS) for Atlantic salmon (Salmo salar L.). In this descriptive study, the level and distribution of selected biochemical plasma analytes from different weight classes of Atlantic salmon reared in commercial RAS facilities maintained in either freshwater or saltwater were determined.MethodsFacility 1 focused on the production of fry to smolt at a salinity of 0.5-2 ppt, and Facility 2 produced fish from smolt to market size. Four fish groups (FG) were included: FG 1-2 in Facility 1 and FG 3-4 in Facility 2. Fish in Facility 1 were sampled monthly, while fish in Facility 2 were sampled at varying intervals (between 4 and 19 weeks) to determine selected biochemical analytes. The study spanned 100-250 days, depending on the fish group. Biochemical analyses included sodium, chloride, potassium, osmolality, calcium, magnesium, total protein, albumin, and globulin. In addition, water quality parameters measured included temperature, salinity, NH4-N, NO2, NO3, color, turbidity, alkalinity, CO2, H2S, and gas pressure.ResultsResults indicated that selected blood analytes of Atlantic salmon were influenced by the production environment (freshwater or saltwater). In addition, there was an effect of fish weight, but variable for the different analytes. Water quality parameters varied with time and system; however, were within acceptable ranges in both production environments. No clear impact biochemical values were found from variations in water quality parameters.DiscussionThese results underscore the need for future research into system/environment-specific reference intervals and a better understanding of how fish weight impacts clinical chemical parameters. Factors that encompass water quality, management practices, fish strain/batch (i.e., stress tolerance), and the physiological status of the fish need to be considered and can influence obtained reference intervals. A threshold for acceptable prevalence and degree of exterior deviations should be defined. Reference values should then be compared to analyte levels in fish with known diseases to assess the diagnostic value of blood sampling.